Regulation of Postharvest Tomato Fruit Ripening by Endogenous Salicylic Acid - Changwal, Chunoti; Shukla, Tushita; Hussain, Zakir; Singh, Neera; Kar, Abhijit; Singh, Virendra P.; Abdin, M. Z.; Arora, Ajay (Frontiers in Plant Science, 2021)
Exogenous application of salicylic acid (SA) has been known for delaying ripening in many fruit and vegetables. But the function of endogenous SA in relation to postharvest fruit performance is still unexplored. To understand the role of endogenous SA in postharvest fruit ripening of tomato, thirty-three tomato lines were examined for their endogenous SA content, Membrane Stability Index (MSI) and shelf life at turning and red stage of tomato fruit ripening. Six tomato lines having contrasting shelf lives from these categories were subjected further for ethylene (ET) evolution, 1-aminocyclopropane-1-carboxylic acid synthase (ACS), 1-aminocyclopropane-1-carboxylic acid oxidase (ACO), polygalacturonase (PG), pectin methyl esterase (PME), antioxidant assays and lipid peroxidation. It was found that high endogenous SA has a direct association with low ET evolution, which leads to the high shelf life of fruit. High lycopene content was also found to be correlated with high SA. Total antioxidants, PG and PME decreased and lipid peroxidation increased from turning to red stage of tomato fruit development. Further, these lines were subjected to expression analysis for SA biosynthesis enzymes viz. SlICS and SlPAL. Real-time PCR data revealed that high shelf life lines have high SlPAL4 expression and low shelf life lines have high SlPAL6 expression. Based on the results obtained in this study, it was concluded that endogenous SA regulates ET evolution and shelf life with the aid of antioxidative defense system, and SlPAL4, and SlPAL6 genes play significant but opposite role during fruit ripening.